ANALYSIS OF HIERARCHY OF INFLUENCE ON ISSUES IN EACH ESG PILLAR ON THE FIRM VALUE IN INDONESIAN MINING COMPANIES THROUGH AN ARTIFICIAL NEURAL NETWORK APPROACH - Syahrul Aziz, Muhammad
In recent decades, increased public attention to corporate social responsibility has heightened stakeholders' expectations regarding corporate ESG performance. The value of mining companies in Indonesia is often defined by their concern for environmental, social, and governance issues. This study aims to determine the significance of the influence of issues in each ESG pillar, both simultaneously and partially, on the firm value of mining companies in Indonesia, as well as the hierarchy of their influence contributions. Data on ESG issues and Tobin's Q over 8 years (2015-2022) from 7 mineral and coal mining companies were obtained from Bloomberg and analyzed using Hypothesis Testing and Artificial Neural Network (ANN). The results of the study include: (A) All issues in each ESG pillar have a significant simultaneous influence on the firm value of mining companies in Indonesia; (B) The issues identified as having a significant partial influence on the firm value of mining companies in Indonesia are Air Quality (-), GHG Emissions Management (+), Community Rights & Relations (-), Ethics & Compliance (-), Audit (+), dan Shareholder Rights (+); The hierarchy of the influence contributions of ESG issues, as mentioned in point (B), is (1) Audit, (2) GHG Emissions Management, (3) Community Rights & Relations, (4) Air Quality, (5) Ethics & Compliance, (6) Shareholder Rights.